2011
DOI: 10.1038/cdd.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 regulates SCF expression to modulate PKBα activity that protects keratinocytes from ROS-induced apoptosis

Abstract: Dysregulated reactive oxygen species (ROS) generation contributes to many human pathologies, including cancer and diabetes. During normal wound repair, inflammation-induced ROS production must be tightly controlled, but the mechanisms reining their generation remain unclear. Herein, we show that transforming growth factor b-activated kinase 1 (TAK1) directly regulates stem cell factor (SCF) expression, which activates the protein kinase B (PKB)a pro-survival pathway in a cell-autonomous manner to protect kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…4A). In addition, production of reactive oxygen species (ROS), which is under the control of TAK1 signaling in other cell types (53), was undisturbed in TAK1-deficient DCs (SI Appendix, Fig. S3).…”
Section: Tak1-dependent Pro-and Antiapoptotic Signaling Mechanisms Inmentioning
confidence: 99%
“…4A). In addition, production of reactive oxygen species (ROS), which is under the control of TAK1 signaling in other cell types (53), was undisturbed in TAK1-deficient DCs (SI Appendix, Fig. S3).…”
Section: Tak1-dependent Pro-and Antiapoptotic Signaling Mechanisms Inmentioning
confidence: 99%
“…This is especially useful in psoriasis research so that epidermal factors can be isolated and studied alone, without any immune related effects. Using this setup, we found that TAK1 kd OTC epidermis displayed significantly higher ROS levels with an increased incidence of keratinocyte cell death (Lam et al, 2011). This suggests that TAK1 kd keratinocytes succumbed to ROS-induced keratinocyte death even in normal tissue development.…”
Section: Ros-induced Oxidative Damage Of Keratinocytes As Initiating mentioning
confidence: 71%
“…Interestingly, we have found that the wound expression of transforming growth factor-(TGF-) activated kinase 1 (TAK1), a downstream signaling player of TNF-, coincides with the pattern of ROS production, with peak expression also at 3-7 days post-injury (Lam et al, 2011). Like PPAR / , TAK1 activity is most likely affected by TNF-induction in wounding.…”
Section: Ros-induced Oxidative Damage Of Keratinocytes As Initiating mentioning
confidence: 99%
See 1 more Smart Citation
“…SCF is also found in the dermis during the early phase of normal wound closure but its level declines thereafter [39]. Additionally, SCF has been shown to function in antiapoptosis of keratinocytes during wound closure [40]. It has been reported that human skin keratinocytes and fibroblasts express Flt3-L [41].…”
Section: Discussionmentioning
confidence: 99%